Low fucose containing bacterial polysaccharide facilitate mitochondria‐dependent ROS‐induced apoptosis of human lung epithelial carcinoma via controlled regulation of MAPKs‐mediated Nrf2/Keap1 homeostasis signaling. Issue 12 (30th October 2014) - Chowdhury, Sougata Roy; Sengupta, Suman; Biswas, Subir; Sen, Ramkrishna; Sinha, Tridib Kumar; Basak, Ratan Kumar; Adhikari, Basudam; Bhattacharyya, Arindam
<x xml:space="preserve">Abstract</x> Reactive oxygen species (ROS), the key mediators of cellular oxidative stress and redox dysregulation involved in cancer initiation and progression, have recently emerged as promising targets for anticancer drug discovery. Continuous free radical assault upsets homeostasis in cellular redox system and regulates the associated signaling pathways to mediate stress‐induced cell death. This study investigates the dose‐specific pro‐oxidative behavior of a bacterial fucose polysaccharide, which attenuated proliferation of different cancer cells. In the fermentation process, Bacillus megaterium RB‐05 [GenBank Accession Number HM371417] was found to biosynthesize a polysaccharide with low‐fucose content (4.9%), which conferred the maximum anti‐proliferative activity (750 µg/mL) against human lung cancer epithelial cells (A549) during preliminary screening. Structural elucidation and morphological characterization of the duly purified polysaccharide was done using HPLC, GC‐MS, 1H/13C NMR, and microscopy. The polysaccharide exhibited concentration‐ and time‐dependent anti‐proliferative effects against A549 cells by inducing intracellular ROS level and regulating the mitochondrial membrane‐permeability following the apoptotic pathway. This process encompasses activation of caspase‐8/9/3/7, increase in the ratio of Bax/Bcl2 ratio, translocation of Bcl2‐associated X protein (Bax) and cytochrome c, decrease in expression of anti‐apoptotic members of Bcl2 family, and phosphorylation of mitogen activated protein kinases (MAPKs). Apoptosis was attenuated upon pretreatment with specific caspase‐inhibitors. Simultaneously, during apoptosis, the ROS‐mediated stress as well as activated MAPKs triggered nuclear translocation of transcription factors like nuclear factor (erythroid‐derived)‐like 2 (Nrf2) and promoted further transcription of downstream cytoprotective genes, which somehow perturbed the chemotherapeutic efficacy of the polysaccharide, although using CuPP, a chemical inhibitor of HO‐1, apoptosis increased significantly (P < 0.05). © 2014 Wiley Periodicals, Inc.